2004
DOI: 10.1590/s0100-879x2004000800018
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species and angiotensin II signaling in vascular cells: implications in cardiovascular disease

Abstract: Diseases such as hypertension, atherosclerosis, hyperlipidemia, and diabetes are associated with vascular functional and structural changes including endothelial dysfunction, altered contractility and vascular remodeling. Cellular events underlying these processes involve changes in vascular smooth muscle cell (VSMC) growth, apoptosis/anoikis, cell migration, inflammation, and fibrosis. Many factors influence cellular changes, of which angiotensin II (Ang II) appears to be amongst the most important. The physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
155
0
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(165 citation statements)
references
References 57 publications
5
155
0
5
Order By: Relevance
“…Oxidation-induced impairment of NO also results in reduced opposition to the vasoconstrictive and hypertensive effects of angiotensin II. Angiotensin II decreases NO bioavailability by promoting oxidative stress [172].…”
Section: Hypertension (Ht)mentioning
confidence: 99%
“…Oxidation-induced impairment of NO also results in reduced opposition to the vasoconstrictive and hypertensive effects of angiotensin II. Angiotensin II decreases NO bioavailability by promoting oxidative stress [172].…”
Section: Hypertension (Ht)mentioning
confidence: 99%
“…Reactive oxygen species (ROS) produced by inflammatory cells and cells of the vasculature increase activity of one or more signaling molecules, including MMP, and cause lipid peroxidation and tissue damage. 7,8 ROSs are believed to be the major component of the mechanisms that contribute to AAA. 7,8 The metabolism of fatty acids by cyclooxygenase (COX), lipoxygenase, and cytochrome P450 (CYP) enzymes results in the generation of ROS, 8,9 and ROS generated via the activation of NADPH oxidase appears to play a major role in the development of AAA.…”
mentioning
confidence: 99%
“…7,8 ROSs are believed to be the major component of the mechanisms that contribute to AAA. 7,8 The metabolism of fatty acids by cyclooxygenase (COX), lipoxygenase, and cytochrome P450 (CYP) enzymes results in the generation of ROS, 8,9 and ROS generated via the activation of NADPH oxidase appears to play a major role in the development of AAA. 10 Previously, we have shown that Ang IIeinduced vascular smooth muscle cell (VSMC) migration, proliferation and hypertrophy, 11 and hypertension 12 depend on CYP1B1, 11,12 a heme-thiolate monooxygenase that is expressed in extrahepatic tissues, including those in the cardiovascular system, 13 and is involved in activating NADPH oxidase and generating ROS.…”
mentioning
confidence: 99%
“…Under pathological conditions, ROS contribute to vascular dysfunction and remodeling through oxidative damage. 32 Ang II-stimulated endothelial NADPH oxidase activity is regulated through phosphorylation of p47/phox. 33 After administration of Ang II to rats for 7 days, the activity and the expression of NADPH oxidase was increased by a protein kinase C-dependent mechanism.…”
Section: Discussionmentioning
confidence: 99%